The burden of German history : a transatlantic life - Jarausch, Konrad H. (Konrad Hugo), 1941- (Berghahn Books, 2023)
"As one of the leading historians of the post-1956 generation and an internationally acclaimed scholar for the past five decades, Konrad H. Jarausch's autobiography presents a sustained academic reflection on the post-war German effort to cope with the guilt of the Holocaust amongst a generation of historians too young to have been perpetrators. Ranging from his war-time childhood in a chaotic country, to Americanization as a foreign student, and concluding with his mentorship of PhDs as a respected international scholar, he weaves together a self-critical historiography of a twentieth-century Germany that was wrestling with the responsibility for war and genocide. This self-reflexive work explores a wide range of topics including the development of German historiography and methodological debates, the interdisciplinary teaching efforts in German studies, and the development of scholarly organizations and institutions"-- Provided by publisher.
Keywords: Jarausch, Konrad H. -- (Konrad Hugo), -- 1941- -- author.; Jarausch, Konrad H. -- (Konrad Hugo), -- 1941-; Holocaust, Jewish (1939-1945) -- Historiography.; Historians -- Germany -- Biography.; Historians -- United States -- Biography.; Germany -- Historiography -- 20th century.; Germany -- Study and teaching -- History -- 20th century.; Germany -- History -- 20th century.; Holocauste, 1939-1945 -- Historiographie.; Historiens -- États-Unis -- Biographies.; Allemagne -- Histoire -- 20e siècle.; HISTORY / Europe / Germany.; Education; Historians; Historiography; Germany; United States; 1900-1999; Electronic books.; Biographies; History